Effects of Dark Chocolate and Milk Chocolate consumption on Sub foveal Choroidal Thickness in healthy young subject: A Randomized double-blind Cross over Study: Oral Presentation - Experimental Study - Ophthalmologist - LA ODE HAMZAH; YUNITA, MD; BATARI TODJA UMAR, MD (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Dark Chocolate consumption was known to effect blood flow and to date there is little information about this effect to human eye. We aim to compare the effect of consuming dark chocolate (DC) and milk chocolate (MC) on sub foveal choroidal thickness (SFCT) and blood pressure (BP) in healthy young subject Methods : A randomized double blind cross over study was used. We randomly assigned subjects into two group. First group consumed DC and then MC at least 72 hours later and the second group consumed MC and then DC. BP and SFCT was measured at baseline, 30 minutes and 2 hours after consumption for each group Results : Data from two group (Group A; 40 eye/20 subject, age 26 -36 years and group B; 40 eye/20 subject, age 27 -34 years) were collected. There was an increase on SFCT at 30 minutes (DC 11.05 ± 13.720 μm, p>0.01; MC 4.40 ± 8.040 μm, p>0.01) and 2 hours (DC 23.45 ± 11.581 μm, p>0.01; MC 9.92 ± 11.288 μm, p>0.01) after consumption compare to baseline. There were no changes found on BP and there was no correlation found between BP and SFCT changes Conclusion : This study found that there was a significant increase in SFCT especially in DC consumption in 30 minute and 2 hours after consumption. There were no changes in BP and No correlation was found between BP and SFCT changes